Biochemical physiological and molecular aspects of human nutrition - Stipanuk, Martha H. (Elsevier, 2019)
A scientific look at the biological bases of human nutrition. Covering advanced nutrition with a comprehensive, easy-to-understand approach, Biochemical, Physiological, and Molecular Aspects of Human Nutrition, 4th Edition, focuses on nutrition at the molecular, cellular, tissue, and whole-body levels. Written by Martha Stipanuk, Marie Caudill, and a team of nutrition experts, the text addresses nutrients by classification, and describes macronutrient function from digestion to metabolism. This edition includes the most current recommendations from the Dietary Guidelines for Americans, plus coverage of the historical evolution of nutrition and information on a wide range of vitamins, minerals, and other food components.